2013
DOI: 10.1007/978-3-642-40104-6_7
|View full text |Cite
|
Sign up to set email alerts
|

Coloring Hypergraphs Induced by Dynamic Point Sets and Bottomless Rectangles

Abstract: Abstract. We consider a coloring problem on dynamic, one-dimensional point sets: points appearing and disappearing on a line at given times. We wish to color them with k colors so that at any time, any sequence of p(k) consecutive points, for some function p, contains at least one point of each color.We prove that no such function p(k) exists in general. However, in the restricted case in which points appear gradually, but never disappear, we give a coloring algorithm guaranteeing the property at any time with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 21 publications
1
33
0
Order By: Relevance
“…Motivated by these, bottomless rectangles are regarded for small values in [11,12] and polychromatic k-colorings in [1]. In this paper we place bottomless rectangles in our abstract context and pose some further problems about them.…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by these, bottomless rectangles are regarded for small values in [11,12] and polychromatic k-colorings in [1]. In this paper we place bottomless rectangles in our abstract context and pose some further problems about them.…”
Section: Introductionmentioning
confidence: 99%
“…It can be expressed as coloring points appearing on a line in such a way that at all times any interval containing p(k) points contains one point of each color, or equivalently, coloring point sets in the plane such that every bottomless rectangle containing p(k) points contains a point of each color. In [5] it is shown that in this case a linear upper bound on p(k) can be achieved with a semi-online coloring algorithm or equivalently a sweeping line algorithm. 4…”
Section: 2mentioning
confidence: 99%
“…This setting can be thought of as points appearing on a line, and we want to color the points with k colors such that at any time, any set of p(k) consecutive points contains at least one of each color. This problem has been studied by a number of authors, whose results were compiled in a joint paper [5]. In particular, they showed that under this restriction, we have 1.6k p(k) 3k−2.…”
Section: Theorem 3 ([19]mentioning
confidence: 99%
“…It can be expressed as coloring points appearing on a line in such a way that at all times any interval containing p(k) points contains one point of each color, or equivalently, coloring point sets in the plane such that every bottomless rectangle containing p(k) points contains a point of each color. In [5] it is shown that in this case a linear upper bound on p(k) can be achieved with a semi-online coloring algorithm or equivalently a sweeping line algorithm. 4 …”
Section: Corollarymentioning
confidence: 99%